Oh, Canada [videorecording (DVD)] - Schrader, Paul, 1946-; Gere, Richard, 1949-; Thurman, Uma; Imperioli, Michael, 1966-; Elordi, Jacob, 1997-; Wonder, Andrew; Phosphorescent (Musician); Banks, Russell, 1940-2023 (Kino Lorber, 2025)
On the outside Leonard Fife is a successful documentary filmmaker, a semifamous left-wing figure in Canada, where he fled to from New England in 1968, supposedly to avoid the draft. He resides in a well-appointed Montreal apartment with Emma, his wife and producer of 40 years, and has managed to be both materially comfortable and morally righteous. But at 78, ill and on the verge of death, he's now consumed by the need to confess that his life is as riddled with lies and betrayal as his body is with cancer.